Infância sobrecarregada: excesso de estudos e atividades extracurriculares na vida da criança - FERREIRA, Ana Paula Maia (2019)
In this bibliographical research of qualitative approach, we deal with the overload of studies and extracurricular activities in childhood. Induced and driven by the capitalist logic of education, families and schools, end up imposing an intense routine of activities on children's lives, which aims to anticipate their learning, prepares them early for the demands of the market and of life in society, in order to achieve excellence in performance throughout the training, and consequently reach a promising future. In this sense, we present the problem of this work in the form of a question: What consequences does the overload of studies and extracurricular activities have on children? The theoretical framework of this research consisted of Ariès (2017); Postman (2012); Kramer (2000); Rousseau (2004); Menezes (2016), authors who make dialogues about childhood. Sampaio, Santos e Mesquida (2002); Cardozo et al. (2017), which address education in the neoliberal logic. Elkind (2004); Santana (2017) which discuss the social pressures to which children are exposed in contemporary times. As a general objective, the intention of this study was to investigate the consequences of the overload of activities for the life of the child. The results indicate that the excessive burden of school and out-of-school tasks can provide a denial of the child's right to live his childhood fully, compromising free time and playing, leading to psychoemotional manifestations which can interfere in the development and learning of the child.